Epidemiological study of tuberculosis in Macassar Camp - Mohammed, Ashraf; Prinsloo, F. R.; Donald, P. R. (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MSc (Community Health))--University of Stellenbosch. 1995.